2020
DOI: 10.4103/jfmpc.jfmpc_1236_19
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-biochemical profile of sick children with severe acute malnutrition

Abstract: Objective: Severe acute malnutrition (SAM) classified as edematous and marasmus, however, Kwashiorker represents the most severe phenotype of edematous malnutrition. The aim of this study was to describe the clinico-biochemical profile in sick children with severe acute malnutrition. Materials and Methods: This is a descriptive cross-sectional study, which included children aged 6 to 60 months, fulfilling the World Health Organization (WHO) criteria of severe acute maln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In addition, malnourished children are three times more likely to develop hyponatremia than their counterparts. This finding is in line with studies conducted in India [ 33 ], Bangladesh [ 34 ], and Kenya [ 21 ]. This may be due to severely malnourished children; most children have excess total body sodium despite low serum sodium levels thus, masking sodium overload [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, malnourished children are three times more likely to develop hyponatremia than their counterparts. This finding is in line with studies conducted in India [ 33 ], Bangladesh [ 34 ], and Kenya [ 21 ]. This may be due to severely malnourished children; most children have excess total body sodium despite low serum sodium levels thus, masking sodium overload [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, in the present study, we revealed that at the time of admission, edematous children had significantly lower concentration levels of RBP, TTR, ALB, TRF, and Hg, than the non-edematous group, which has also been demonstrated in previous studies 27,28 . Furthermore, a recent study has revealed serious metabolic disturbance in the edematous child than those without edema 29 . In our study, at discharge, all nutrition-related proteins increased significantly to normal in both groups (Table 4) reflecting satisfactory nutritional recovery except for Hg which remained below normal in the non-edematous group.…”
Section: Discussionmentioning
confidence: 99%